Genital cutting: protecting children from medical, cultural, and religious infringements - Hodges, Frederick M.; Milos, Marilyn Fayre; Denniston, George C. (Springer Netherlands, 2013)
Every year, across the globe, an estimated 13.3 million boys and 2 million girls are involuntarily subjected to genital cutting. Both male and female genital cutting persist, generating a multi-billion-dollar-a-year industry that is defended by its proponents with dubious studies, manipulated statistics, and an appeal to "custom." Physicians and parents alike have been misled into believing that these mutilations are beneficial, necessary, and harmless. Today, flawed studies have allowed the promotion of circumcision as a way of combating HIV/AIDS in Africa, an experiment that failed in the USA, where a half-million circumcised males have succumbed to AIDS. These facts notwithstanding, the public and legal outcry against these abuses is increasing. For instance, the high court in Cologne, Germany ruled in 2012 that circumcision harms the child, that the harm is irreversible, that it denies the child the right to his own body, and that circumcision denies the individual the right to choose his own religion. Thus, the issue of circumcision has expanded beyond the arena of medicine and is firmly established as a human rights and legal problem. The contributors to this volume, an international panel of experts in the fields of medicine, law, ethics, anthropology, sociology, history, religion, and politics, thoroughly examine and elucidate this violation of human rights.